Analysis of the successfulness of wolverine (Gulo gulo) depredation control in Västerbotten County - Vretling, Fredrika (2016)
During the last five years, permitted quota of wolverine to be removed by depredation control have not been filled in the County of Västerbotten. Few hunting attempts have been successful. Because of this, issues regarding the depredation of reindeer may not be solved. The aim of this study was to evaluate the successfulness of hunting of wolverines for depredation control in Västerbotten County. Results from this study show that interviewees viewed depredation control as a positive management tool, but that possibilities for hunting were rather limited. The critical factor for a successful outcome of wolverine hunting was to find fresh tracks. However, possibilities for finding tracks were limited by weather and snow conditions. All hunting methods used were looked upon as being effective if they were conducted when weather and snow conditions were suitable. Hunting with dogs worked well during fall when there was little snow. Hunting by helicopter and snowmobile were most preferred in January, which also was the month where most wolverines where shot. Five out of seven interviewees were positive towards implementing quota harvest of wolverine in the future, if the hunting would be executed by moose hunters during the regular hunting season.